Screens ‘As Representation’ and Screens ‘As Simulation’ in Mainstream Cinema Detection - Virginás, Andrea (The Nordic Journal of Aesthetics, 2016)
Detection in contemporary genre films is in the process of being transformed: viewers see less and less of moving, traveling, and active human bodies entering in interaction and exchanging words. Instead, what takes up a significant part of film time is the view of computer screens, with digitally stored and retrieved traces, meaningful for detection, playing the lead role. One result of this type of detection on screen – rather than detection in the streets or on murder scenes – is that detection is (re)presented as a process happening on the human-computer interface. With reference to Lev Manovich the article asks how the “illusion of navigating through virtual spaces” is recreated, when the context of such an illusion is filmic diegesis defined by genre rules (in this case: detection films), where “the virtual spaces of the screen” should have a direct effect on “the real spaces of filmic diegesis”?